Blended learning in action : a practical guide toward sustainable change - Tucker, Catlin R.; Wycoff, Tiffany; Green, Jason T.. (b)
Blended learning has the power to reinvent education, but transitioning to a blended model is challenging. Blended learning requires a fundamentally new approach to learning as well as a new skill set for both teachers and school leaders. Loaded with research, examples, and resources, Blended Learning in Action demonstrates the advantages a blended model has over traditional instruction when technology is used to engage students both inside the classroom and online. Readers will find Breakdowns of the most effective classroom setups for blended learning; Tips for leaders; Ideas for personalizing and differentiating instruction using technology; Strategies for managing devices in classrooms and schools; Study questions to facilitate professional development and deeper learning. Written with systematic transformation in mind, this is the resource teachers and leaders need to help them shift to a blended learning model and transform education for the 21st century.
Includes bibliographical references (pages 195-198) and index.
Keywords: Blended learning; Educational change